Efforts to Improve Mathematics Learning Outcomes for Elementary School Students by Using Number Card Learning Media - Afifatul Mahfuzah (Jurnal Pendidikan Profesi Guru, 2023)
This research is motivated by the fact that students are less involved in learning, talk a lot when the teacher explains the material, the teacher does not create learning activities that encourage students to be more active in learning. As a result, children are not interested in participating in the teaching and learning process and become bored. This study intends to improve the mathematics learning outcomes of elementary school students by using number card media. Fifth grade elementary school students were used as research subjects. Classroom Action Research was carried out in two cycles. If this research meets the minimum completeness requirements, it is considered successful. The results showed that the completeness of student learning outcomes in cycle one was 68%. While the completeness of student learning outcomes in the second cycle increased to 92%. So it can be concluded that the use of number card media can make multiplication arithmetic operations better for class V, it is proven that the use of number cards as a learning medium can improve the learning outcomes of elementary school students' mathematics.